Aroma-active volatiles and rheological characteristics of the plastic mass during conching of dark chocolate - Guckenbiehl, Yvonne; Martin, Anna; Ortner, Eva; Rothkopf, Isabell; Schweiggert-Weisz, Ute; Büttner, Andrea; Naumann-Gola, Susanne (Food Research International, 2022)
Chocolate conching is a highly complex, thermomechanical process that transforms the aroma and flow properties of a dry starting material. Different conched plastic masses of dark chocolate were characterized. Rheological characterization of plastic masses was performed for the first time using a closed cavity rheometer (CCR). In free cocoa butter derived from the plastic masses, acetic acid, benzaldehyde, (R,S)-(±)-linalool, 2,3,5,6-tetramethylpyrazine, and 2-phenylethanol were quantified by stable isotope dilution analysis (SIDA) and gas chromatography-mass spectrometry. During the conching process, the amount of free cocoa butter increased possibly due to de-agglomeration. The complex viscosity of the plastic mass decreased as a function of conching time. Regarding aroma refinement, the concentrations of all five aroma-active volatiles decreased with increasing conching duration, albeit to varying degrees. The level of acetic acid showed the most pronounced decrease of about 60%, whereas linalool exhibited the lowest decrease in concentration, up to 26%. Overall, a lower polarity or boiling point of the aroma-active volatiles was linked to a stronger decrease in concentration during conching. These data illustrate the influence of conching on texture and the respective aroma changes, which deepens understanding of the conching effect on the sensory quality of dark chocolate.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Aroma concentration; Chocolate flavor; Chocolate texture; Closed cavity rheometer; Free cocoa butter; Plastic conching

Conching of dark chocolate – Processing impacts on aroma-active volatiles and viscosity of plastic masses - Guckenbiehl, Yvonne; Morales Romero, Aurora Magdalena; Haug, Helen; Ortner, Eva; Rothkopf, Isabell; Schweiggert-Weisz, Ute; Büttner, Andrea; Gola, Susanne (Current Research in Food Science, 2024)
The conching process plays a key role in determining the sensory and rheological properties of dark chocolate. To further understand this process, changes in the chocolate mass during plastic conching were investigated on a time-resolved basis with varying conching temperature, shear direction, and with or without the presence of residue from previous trials (pre-charge) on the conche vessel wall. Six selected odorants (acetic acid, benzaldehyde, linalool, 2,3,5,6-tetramethylpyrazine, 2-phenylethanol, 2-phenylethyl acetate) were quantified in fat and particle phases of chocolate masses. Particularly at elevated conching temperature, the odorant concentrations were found to decrease (up to 78.0% in the fat phase). The highest concentrations of desired odorants were determined mostly after conching without pre-charge. During conching, odorants were observed to accumulate increasingly in the fat phase (up to 91.7%) with decreasing odorant polarity. Similarly, it was found that conching temperature and the absence of pre-charge had the highest impact on the rheological properties of the chocolate mass, resulting in lowest and highest complex viscosity, respectively. In conclusion, some positive outcomes of conching, namely the retention of desired odorants and the reduction of viscosity, were inversely related at elevated temperature or in the absence of pre-charge, necessitating compromises to achieve optimal flow properties and flavor. Our results contribute to a deeper understanding of the influence of conching on the quality of dark chocolate by providing insights into the complexity of aroma migration and rheological changes during conching.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Aroma distribution; Chocolate flavor; Closed cavity rheometer; Conching parameters; Gas chromatography-mass spectrometry; Plastic conching

Corrigendum to “Aroma-active volatiles and rheological characteristics of the plastic mass during conching of dark chocolate” [Food Res. Int. 162 (Part B) (2022) 112063] (Food Research International (2022) 162(PB), (S0963996922011218), (10.1016/j.foodres.2022.112063)) - Guckenbiehl, Yvonne; Martin, Anna; Ortner, Eva; Rothkopf, Isabell; Schweiggert-Weisz, Ute; Büttner, Andrea; Naumann-Gola, Susanne (Food Research International, 2023)
The authors regret, to report misleading text passages due to typing errors and would like to correct following parts: When stated in the abstract: “Overall, a lower polarity or boiling point of the aroma-active volatiles was linked to a stronger decrease in concentration during conching.” It should be changed to: “Overall, a higher polarity or lower boiling point of the aroma-active volatiles was linked to a stronger decrease in concentration during conching.” When stated in chapter 3.3.1.: “Considering aroma redistribution processes, this trend supports the hypothesis that aroma migration from nonpolar cocoa butter to more polar phases increases with decreasing polarity of the substances.” It should be changed to: “Considering aroma redistribution processes, this trend supports the hypothesis that aroma migration from nonpolar cocoa butter to more polar phases increases with decreasing LogP of the substances.” When stated in chapter 3.3.1.: “Based on the trend that the most polar substances decrease in concentration most sharply during conching (Table 3), it is conceivable that the investigated volatiles increasingly evaporate from the free cocoa butter into the ambient air with decreasing polarity.” It should be changed to: “Based on the trend that the most polar substances decrease in concentration most sharply during conching (Table 3), it is conceivable that the investigated volatiles increasingly evaporate from the free cocoa butter into the ambient air with increasing polarity.” The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2023-04-14

Distribution and transition of aroma-active compounds in dark chocolate model systems under conching conditions - Guckenbiehl, Yvonne; Ortner, Eva; Rothkopf, Isabell; Schweiggert-Weisz, Ute; Ziegleder, Gottfried; Büttner, Andrea; Naumann-Gola, Susanne (Food Chemistry, 2024)
Understanding mechanisms inside the conche is inevitable for targeted conching. Therefore, distribution and transition of aroma-active volatiles (acetic acid, benzaldehyde, (R,S)-(±)-linalool, 2,3,5,6-tetramethylpyrazine, 2-phenylethanol, and 2-phenylethyl acetate) between the different components of dark chocolate (cocoa butter, cocoa particles, sugar particles) were studied. Different model systems were designed and aroma-analytically analyzed by stable isotope dilution analysis. Diffusion mechanisms of selected aroma-active compounds within the chocolate mass depended on their physico-chemical properties and the mass composition, such as fat content and crystallization state of the sugar particles. The compound accumulation in the fat phase increased with decreasing compound polarity and increasing fat content. In the presence of cocoa particles, a 1.5-fold fat content resulted in a 1.6-fold higher proportional acetic acid concentration in the fat phase. Further, total acetic acid concentrations raised in all model systems containing crystalline sugar or cocoa particles (by 13.8–56.9 %), indicating the formation of free acetic acid.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Acetic acid; Chocolate aroma; Cocoa butter; Cocoa particles; Stable isotope dilution assay; Sugar particles

Refining and conching alter the volatile composition of dark chocolate — Revealing profile changes in aroma-active volatiles and volatile organic compounds - Guckenbiehl, Yvonne; Ortner, Eva; Rothkopf, Isabell; Buettner, Andrea (Journal of Agriculture and Food Research, 2025)
The chocolate volatilome is formed by cocoa variety, growing region, and harvesting season but also by multiple post-harvest processes, namely fermentation, drying, roasting, and conching. To deepen the understanding of aroma changes during chocolate production, aroma-active volatiles and the profile of volatile organic compounds (VOCs) were investigated in cocoa liquor, both after refining in the so-called flakes, and in chocolate after conching. Aroma-active volatiles were analyzed applying gas chromatography-mass spectrometry/olfactometry combined with aroma extract dilution analysis and VOC profiles were screened by gas chromatography-ion mobility spectrometry. Overall, flavor dilution (FD) factors of up to 6 561, which refers to the maximum dilution of the distillates at which the odorants could be perceived, were determined, whereas dimethyl trisulphide, 2,3-diethyl-5-methylpyrazine, 3-(methylthio)propanal, 3-isobutyl-2-methoxypyrazine, 3-methylbutanoic acid, 4-hydroxy-2,5-dimethylfuran-3(2H)-one, γ-decalactone, 3-hydroxy-4,5-dimethylfuran-2(5H)-one, acetic acid, and 3-phenylpropanoic acid were among the aroma-active compounds eliciting the highest FD factors in the samples. Generally, the number of compounds detected, and the FD factors determined decreased along the processing steps, whereas FD factors of aldehydes partially increased as these are generated, inter alia, by lipid oxidation. The influence of processing was likewise mirrored in the VOC profile where conching in particular resulted in decreased VOC intensities. Individual VOC intensities, however, were increased after refining and conching, contributing to a discrimination of the different samples drawn after each processing step. Presumably, a major part of the VOCs detected in our study were not aroma-active. Our results thus provide an insight into the changes in volatile compounds’ composition during chocolate production and deliver a new perspective for monitoring the chocolate manufacturing process.
CRIS-Team Scopus Importer:2025-02-07
Keywords: Aroma; Cocoa liquor; Flakes; Gas chromatography-ion mobility spectrometry; Gas chromatography-mass spectrometry/olfactometry; Identification